2011
DOI: 10.1510/icvts.2010.264853
|View full text |Cite
|
Sign up to set email alerts
|

Right paracardiac mass due to organized pericardial hematoma around retained epicardial pacing wires following aortic valve replacement

Abstract: The use of temporary epicardial pacing wires during cardiac surgery is a routine procedure and has been associated with low morbidity. We describe a rare case of right paracardiac mass due to organized pericardial hematoma with right atrial compression around the epicardial pacing wires left in-situ, presenting three months following aortic valve replacement surgery. The case highlights the fact that such delayed complications can rarely occur around retained epicardial pacing wires following open heart surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…During removal, patients are at risk of ventricular arrhythmias [18] and to a lesser extent bleeding due to injury of nearby structures [19-21]. Also retention of PWs may be complicated by deep seated infections or migration to different structures in the chest [7-9,22,23]. …”
Section: Discussionmentioning
confidence: 99%
“…During removal, patients are at risk of ventricular arrhythmias [18] and to a lesser extent bleeding due to injury of nearby structures [19-21]. Also retention of PWs may be complicated by deep seated infections or migration to different structures in the chest [7-9,22,23]. …”
Section: Discussionmentioning
confidence: 99%
“…An article published in 2008 queried the use of TEPWs;14 in 2009, another article questioned whether retained pacing wires were the culprit for the development of a sternobronchial fistula that arose in a patient following coronary surgery 15. In 2011, a patient suffered from the development of a right paracardiac mass due to an organised haematoma around retained epicardial pacing wires following aortic valve replacement 16. In 2012, another case of migration occurred where the lead travelled from the right ventricular myocardium into the pulmonary artery in a patient who had successfully undergone CABG 13 years prior 17.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients from the study group had localized pericardial hematoma post Bentall procedure and following CABG operation. Kapoor et al [16] reported a case of delayed complications related to retained epicardial pacing wires left in situ with consequent organized pericardial hematoma around the wires presenting three months following aortic valve replacement surgery especially in patients on long term oral anticoagulants. Also there were seven patients with pericardial effusion.…”
Section: Discussionmentioning
confidence: 99%
“…The graft related surgical complications of coronary arteries include spasm [3], graft thrombosis [4] [5], malposition, kinking [5] [6], and iatrogenic complications such as retained clips, aneurysm and pseudoaneurysm of graft and ascending aorta, ostium stenosis and occlusion of coronary artery after Bentall procedure [6]- [9]. The non-graft related surgical complications include pleural and pericardial effusion [10]- [17], sternal and mediastinal infections [16]- [19], mediastinal hematomas [18] [19], and pulmonary embolism [3]- [20]. Many authors have demonstrated that CT is an invaluable tool in the assessment of post-operative complications after CABG as it is accurate, reproducible, short time, but with a diagnostic level of radiation dose to the patient [1]- [9].…”
Section: Introductionmentioning
confidence: 99%